Lixiviación amoniacal del mineral de cobre tipo crisocola utilizando nitrato de amonio. - Roldán Alva, Francisco Lenin (2015)
Leaching was studied in ammonia medium, chrysocolla copper ore type at laboratory level; to determine the extraction efficiency using ammonium nitrate as the leaching agent. For this purpose variables pH, solvent concentration, solid-liquid ratio and the parameters such as temperature, time, particle size and the stirring speed it was felt remain fixed; however, it was obtained at pH 9,5, RS/L1/10 and [NH3]= 6,6792g/L, stirring speed 800 rpm, particle size -# 100(150) microns, Wm= 20 g, time 5 hours, temperature and pressure environmental, a recovery was obtained 45,36 %.